Analisis Pengaruh Rasio NPL, BOPO Dan CAR Terhadap Kinerja Keuangan Pada Bank Umum Konvensional Yang Terdaftar Di BEI - Ningsih, Suhesti; Dewi, Maya Widyana (Jurnal Akuntansi dan Pajak, 2020)
This study aims to analyze the effect of CAR, NPL and BOPO partially or simultaneously on financial performance at banks. The sample in this study is conventional commercial banks listed on the IDX, with samples that meet the sample criteria as many as 22 banks in a period of 3 years. The results of the research F test results of 0,000 indicate that the model is feasible to use. It also proves that the NPL, BOPO and CAR variables together influence the financial performance of commercial banks listed on the IDX. T test results show NPL and BOPO with a significance value of 1.010 and 0.000, this means that NPL and BOPO have a positive effect on the financial performance of commercial banks listed on the IDX while CAR with a t value of 0.682, which means greater than 0.05, the CAR has no effect on the financial performance of commercial banks listed on the IDX. The influence of the NPL, BOPO and CAR variables on the performance of the Bank's financial performance of the remaining 76.5% by 23.5% is influenced by other variables not examined in this study